Frequency of Fetomaternal Outcomes in Severe Preeclampsia: Preeclampsia and Fetomaternal Outcomes - Khattak, Aroosa Usman; Khattak, Saima (Pakistan Journal of Health Sciences, 2024)
Preeclampsia, severe preeclampsia, and eclampsia are hypertension illnesses that occur during pregnancy. The severe spectrum that includes organ failure, unconsciousness, and, sadly, maternal, and fetal deaths, is known as preeclampsia and eclampsia. Objective: To investigate the prevalence of fetomaternal outcomes in severe preeclampsia. Methods: This descriptive cross-sectional study was conducted from February 1st to August 1st, 2021, a descriptive case series was carried out at the Obstetrics and Gynecology Department at Lady Reading Hospital (LRH), Peshawar. A total of 232 pregnant women with severe preeclampsia were included in the research. Several unfavorable fetomaternal outcomes, such as caesarean section, mortality, low birth weight, fetal death, poor Apgar score, preterm birth, and birth asphyxia, were recorded along their course till delivery. Results: The study encompassed women aged 18 to 40, with mean values of 28.14 ± 2.72 years for age, 1.24 ± 1.23 for parity, 36.37 ± 2.17 weeks for gestational age, and 25.86 ± 1.39 kg/m2 for BMI. Among the observed outcomes, cesarean section was noted in 56% of patients, mortality occurred in 8.6% cases, low birth weight in 17.2%, fetal death in 11.2%, low Apgar score in 19%, preterm birth in 8.6%, and birth asphyxia in 7.8%. Conclusions: The results highlight a significant rate of morbidity and death among mothers and perinatals linked to severe preeclampsia. Better prenatal care may be able to delay the onset of severe preeclampsia and eclampsia, which might significantly reduce the risk of negative outcomes.